Gender discrepancies and differences in motor and non-motor symptoms, cognition, and psychological outcomes in the treatment of Parkinson’s disease with subthalamic deep brain stimulation - Hendriks, Martijn; Vinke, Ruben Saman; Georgiev, Dejan (Frontiers in Neurology, 2024)
Available data suggest that there may be gender differences in the effect of STN-DBS in the treatment of Parkinson’s disease (PD). The aim of this study was to review data on gender discrepancies and gender differences in clinical outcomes in PD patients treated with deep brain stimulation of the subthalamic nucleus (STN-DBS). Included were original studies that specifically examined gender discrepancies or gender differences in PD patients with STN-DBS. Men receive more DBS than women, for various indications. The decision-making process for DBS in women compared to men is more influenced by personal preferences and external factors. Motor symptoms improve in both genders, but bradykinesia improves more in men. The postoperative reduction of the levodopa equivalent daily dose seems to be more pronounced in men. Men show more cognitive deterioration and less improvement than women after STN-DBS. Women show more depressive symptoms before surgery, but they improve similarly to men. Men show more improvement in impulsivity and less decrease in impulsive behaviour symptoms than women. Anxiety and personality traits remain unchanged in both genders. Voice quality improves more in men and deteriorates less often than in women. Men gain fat-free mass and fat mass, but women only gain fat mass. Regarding sexual function the evidence is inconsistent. More urinary symptoms improve in women than in men. Pain and restless leg syndrome seems to improve more in men. Regarding quality of life, the evidence seems to be inconsistent, and activities of daily living seems to improve in both genders. Better prospective controlled studies, focusing directly on gender differences in PD patients treated with STN-DBS, are needed to better explain gender differences in STN-DBS for PD.